Heinrich Manns historischer Roman Henri Quatre in der polnischen Rezeption 1936 – 1985 - Dziergwa, Roman (Studia Germanica Posnaniensia, 2018)
The problem of purposefulness of creating historical novels and problems connected with their artistic shape became the subject of critical-literary debate carried on in the 30's of this century in Poland. The people taking part in debates connected their own reflections and thoughts on this subject quite often with critical discussion of the selected historical novels of German emigration writers: Thomas Mann, Alfred Döblin, Alfred Neumann, Lion Feuchtwanger, Hermann Kesten and Henry Mann. The first critical opinions after “Henry IV” was published were typical of Polish literary criticism of those years - it was under great influence of French literature and culture. It is worth mentioning that the genre, i. e. historical novel was distinctly determined, in contradistinction to the then popular biographical novel, by the first reviewers (among others Karol Irzykowski). After the Second World War Henry Mann's novel was published several times. Its critical reviews, especially those written at the beginning of the 50's were, however, written from the point of view of doctrinally understood socrealism and contained numerous simplifications and shallowing of the complex problems of the novel. “Weltanschauung weaknesses” were reproached and the reviewers said how it might be better written. This attitude changed in principle in the second half of the 50's. Henry Mann's innovations were begun to be perceived in confrontation with the real invasion of fashionable biographical novels at this time in Europe. The authors of critical reviews thought that Mann opposed the temptation of making the past up to date, he also avoided excessive psychologism. In Polish German studies Henry Mann's novel was treated only marginally.